Optogenetic approaches for the analysis of the role of dopaminergic neurotransmission in the development of alcohol dependence: from correlations to mechanisms - E. A. Budygin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Despite many years of work on dopaminergic mechanisms of alcohol addiction, much of this evidence remains mostly correlative in nature. Fortunately, the latest technological advances have provided the opportunity to explore the causal role of neurochemical changes within brain regions involved in addictive behaviors. In this work using optogenetics, we have attempted to answer the question of how dopamine release dynamics control the motivational component of alcohol drinking behavior.